Speckle noise reduction of synthetic aperture radar imagery using Kalman filters. - Geling, Gary W. (University of Ottawa (Canada), 1995)
Synthetic aperture radar (SAR) imagery is gaining increased usage as more systems become available and more applications are being developed. An "unfortunate" problem with SAR imagery is the high level of noise, often called speckle. The speckle effects reduce the utility of SAR imagery a great deal. This thesis will address the causes of speckle and many of the current methods that are used to reduce the speckle noise. Kalman filtering methods will then be adapted for use on SAR imagery taking into account the special properties of this type of filter and images.
Keywords: Engineering, Electronics and Electrical.